Optimasi Pemilihan Tenaga Kerja Bagang dengan AHP dan Weighted Product - Maulana, Sahrul; Pasrun, Yuwanda Purnamasari; Muchtar, Mutmainnah; Yuandi, Intan Anuggrah (JISTech : Journal of Information Systems and Technology, 2025)
Choosing the appropriate personnel for bagang fishing units is essential for facilitating effective and efficient field operations. Nevertheless, selection processes dependent on subjective judgment frequently yield unsatisfactory outcomes. This study seeks to establish a decision support system utilizing a mix of the Analytical Hierarchy Process (AHP) and Weighted Product (WP) approaches to identify the optimal candidates. AHP calculates the hierarchical weight of each criterion by pairwise comparisons, whereas WP ranks alternatives based on preference values. The evaluation employs five primary criteria: work experience, physical endurance, discipline, capacity for night shifts, and technical skills. The results indicate that the most qualified individuals were objectively chosen, with A3, A7, and A5 receiving the greatest preference scores. This model provides a systematic framework for decision-making and is applicable in analogous circumstances necessitating multi-criteria selection. The implemented system has demonstrated an improvement in accuracy and transparency in labor recruiting in the conventional fishing sector.